Idiopathic hypereosinophilic syndrome presenting with recalcitrant oral and genital ulcers responding well to thalidomide - Sahana M Srinivas; Pooja G Chebbi; Sanjay K Shivappa (Wolters Kluwer Medknow Publications, 2023)
Hypereosinophilic syndrome is a myeloproliferative disorder characterized by abnormal accumulation of eosinophils in the blood or peripheral tissues. It is uncommonly seen in children. We describe a 14-year-old girl diagnosed with idiopathic hypereosinophilic syndrome presenting with recurrent, painful oral and genital ulcers, hepatosplenomegaly along with consistently high eosinophil count and leucocytosis. Genetic studies showed negative for FIPIL-PDGFRA fusion gene. Mucosal ulcers were recalcitrant to conventional therapy and responded well to thalidomide.